(3LQjeI ZSd GdCehGd Hjf GdhSGFW GdEdcJQhfjI hfUhU GdJTQjYs - (3YHO GdaJGM Hjhej(B, (3MLGRjs ((3GdEScfOQjI(B:s (3OGQ GdacQ GdLGeYj(B,s, 2005)
(3LQjeI ZSd GdCehGd Yf WQjb GdhSGFW GdEdcJQhfjI(B- (3LQjeI ZSd GdCehGd YHQ GdCfJQfJ(B- (3GdeUGQa GdEdcJQhfjI(B- (3GdfbhO GdEdcJQhfjI hZjQgG ef hSGFd ZSd GdCehGd dOi GdHfhc GdEdcJQhfjI(B- (3GdhSGFW GdEdcJQhfjI aj LQjeI ZSd GdCehGd(B- (3LQjeI ZSd GdCehGd aj GdbGfhf GdeUQj(B.s
Keywords: (3GdJLGQI GdEdcJQhfjI(B- (3bhGfjf hJTQjYGJ(B- (3eUQs; (3LQGFe GdCehGd(B- (3bhGfjf hJTQjYGJ(B- (3eUQs; (3ZSjd GdCehGd(B- (3bhGfjf hJTQjYGJ(B- (3eUQs